The Gun in Central Africa: A History of Technology and Politics - Macola, Giacomo (New African Histories, 2016)
Why did some central African peoples embrace gun technology in the nineteenth century, and others turn their backs on it? In answering this question, The Gun in Central Africa offers a thorough reassessment of the history of firearms in central Africa. Marrying the insights of Africanist historiography with those of consumption and science and technology studies, Giacomo Macola approaches the subject from a culturally sensitive perspective that encompasses both the practical and the symbolic attributes of firearms. Informed by the view that the power of objects extends beyond their immediate service functions, The Gun in Central Africa presents Africans as agents of technological re-innovation who understood guns in terms of their changing social structures and political interests. By placing firearms at the heart of the analysis, this volume casts new light on processes of state formation and military revolution in the era of the long-distance trade, the workings of central African gender identities and honor cultures, and the politics of the colonial encounter.